On the robustness of the r-process in neutron-star mergers against variations of nuclear masses. (July 2016) - Mendoza-Temis, J J; Wu, M R; Martínez-Pinedo, G; Langanke, K; Bauswein, A; Janka, H-T; Frank, A
Abstract: r-process calculations have been performed for matter ejected dynamically in neutron star mergers (NSM), such calculations are based on a complete set of trajectories from a three-dimensional relativistic smoothed particle hydrodynamic (SPH) simulation. Our calculations consider an extended nuclear reaction network, including spontaneous, β - and neutron-induced fission and adopting fission yield distributions from the ABLA code. In this contribution we have studied the sensitivity of the r-process abundances to nuclear masses by using diferent mass models for the calculation of neutron capture cross sections via the statistical model. Most of the trajectories, corresponding to 90% of the ejected mass, follow a relatively slow expansion allowing for all neutrons to be captured. The resulting abundances are very similar to each other and reproduce the general features of the observed r-process abundance (the second and third peaks, the rare-earth peak and the lead peak) for all mass models as they are mainly determined by the fission yields. We find distinct differences in the predictions of the mass models at and just above the third peak, which can be traced back to different predictions of neutron separation energies for r-process nuclei around neutron number N = 130.